(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This work presents the design and simulation of a universal smart battery charger capable of charging different types of rechargeable batteries, including Nickel-Cadmium (NiCd), Nickel-Metal Hydride (NiMH), Sealed Lead-Acid (SLA), and rechargeable alkaline batteries. The system is designed to automatically or manually select the appropriate charging algorithm and parameters for each battery chemistry, ensuring safe and efficient charging performance. A microcontroller-based control system is used to monitors battery parameters such as voltage, current, and temperature in real-time. The system applies the correct charging method depending on the type of battery selected —constant-current (CC), constant-voltage (CV), or trickle charge—along with intelligent termination techniques such as −ΔV detection, temperature rise monitoring (ΔT/Δt), or current tapering. Overvoltage, overcurrent, reverse polarity, and thermal shutdown safeguards were integrated for safety and reliability. A user interface with indicators and selection buttons was incorporated for easy operation and status monitoring. The developed system provides a cost-effective solution for charging a wide range of rechargeable batteries.